The application of dynamic password technology based on ECC algorithm in mobile payment. (1st January 2014) - Wang, Chundong; Feng, Chaoran
This paper puts forward a security scheme of mobile payment based on the method of ECC algorithm and dynamic password technology against the security issues in mobile payment system. In terms of the input on mobile terminal, we use a dynamic input method to provide payment password and realise the second encryption for payment password to ensure security of payment password on mobile terminal. Through the above assurance measures, the paper provides both convenient and reliable new technology. This paper analyses the security of the system and encryption speed at the end.